Grant Hackett's Full Stroke (Frontal View) at 270 m of His Silver Medal 400 m Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Grant Hackett's full stroke (frontal view) at 270 m of his silver medal 400 m Race at the 1998 Perth World Championships. Grant Hackett is a very fine swimmer. However, two aspects are of concern about his stroking. The first is his head lifting and rotation actions. They cause streamlining to be reduced and produce considerable drag resistance. The second feature is the period in each stroke where little propulsive force seems to be developed. Those inertial lags are fatiguing and also reduce the swimmer's efficiency, factors that are undesirable for a distance swimmer.